Drought management norms: is the Middle East and North Africa Region managing risks or crises? - Jedd, T.; Fragaszy, S. R.; Knutson, C.; Hayes, M. J.; Belhaj Fraj, M.; Wall, N.; Svoboda, M.; McDonnell, Rachael (SAGE Publications, 2021)
The Middle East and North Africa region experiences severe socioeconomic and political impacts during droughts and faces increasing drought risk in future climate projections. The UN Office for Disaster Risk Reduction’s Sendai Framework and the International Drought Management Programme provide a global standard (a norm) to manage droughts through natural hazard risk reduction approaches. We use participatory engagement to evaluate whether norm diffusion has taken place in four countries. Data were collected in interviews, focus groups, workshops, and policy documents. Analysis reveals incomplete norm diffusion; stakeholders subscribe to relevant values, but national policies and implementation do not fully reflect the norm. Process tracing reveals that the availability of drought early warning data is a key barrier to risk reduction. Further more, a drought early warning system would not be feasible or sufficient unless paired with policy measures and financial mechanisms to reduce the political and economic costs of a drought declaration.